The Influence of Type of Display (Visual and Audio) and Gender Differences on Positive Mood in Early Adolescents - Samudra, Tegar Bagus; Zulfian, Moch. Rifqi Putra; Purnama, Sandy Putra Wahyu; Balgies, Soffy (International Conference on Sustainable Health Promotion, 2025)
This study aimed to examine the effect of media exposure and gender on positive mood among early adolescents. A true experimental design with a 2x2 factorial model was employed, involving two independent variables: type of media exposure (visual and audio) and gender (male and female). Participants were early adolescents aged 10–19 years, randomly assigned to ensure balanced distribution across groups. The Positive and Negative Affect Schedule (PANAS), focusing only on the positive dimension, was administered as a pre-test and post-test to measure changes in positive mood. Data were analyzed using two-way Analysis of Variance (ANOVA). The results revealed no significant main effects of media exposure type or gender on positive mood, nor a significant interaction effect between the two variables. These findings suggest that positive mood among early adolescents is not influenced by media type or gender, but may be shaped by other factors such as initial emotional state, individual media preferences, or social context.